Unintentional injury prevention in American Indian and Alaska Native communities: a scoping review of the Indian Health Service Primary Care Provider newsletter - Wendy Shields; Anne Kenney; Evelyn Shiang; Rebecca Malizia; Holly Billie (BMC, 2024)
Abstract Background Unintentional injuries disproportionately impact American Indian and Alaska Native (AI/AN) populations. Developing effective and culturally tailored data collection and intervention programs requires an understanding of past prevention efforts in AI/AN communities, but limited peer-reviewed literature on the topic is available. This scoping review aims to summarize efforts that have been published in the Primary Care Provider newsletter, a source of gray literature available through the Indian Health Service. Methods The research team obtained all injury related articles in the Provider newsletter and excluded those that did not describe an unintentional injury prevention effort. Included articles were organized chronologically and by topic, and outcomes were described in a data abstraction form. Results A total of 247 articles from the Provider newsletter were screened, and 68 were included in this review. The most number of articles were published in 2007 (n = 15). Many focused not specifically on one tribal community but on the AI/AN community as a whole (n = 27), while others reported that certain tribes were the focus of study but did not identify tribes by name (n = 24). The following is a list of 14 tribal communities explicitly mentioned: Omaha, Cherokee, Ute, Yakama, Chippewa, Apache, Ho-Chunk, The Crow Tribe, Tohono O'odham Nation, Fort Mojave Tribe, Chemehuevi Tribe, The Rosebud Tribe, Navajo, and The Pueblo of Jemez. Published unintentional injury prevention efforts have covered the following 7 topics in AI/AN communities: falls, motor vehicle crashes, poisonings, improving data, burns, children, and other. Conclusion This scoping review makes available and searchable information on injury prevention work conducted in and for AI/AN communities that is not currently found in the peer-reviewed literature.